Mitochondrial Function and Parkinson’s Disease: From the Perspective of the Electron Transport Chain - Li, Jeng-Lin; Lin, Tai-Yi; Chen, Po-Lin; Guo, Ting-Ni; Huang, Shu-Yi; Chen, Chun-Hong; Lin, Chin-Hsien; Chan, Chih-Chiang (Frontiers in Molecular Neuroscience, 2021)
Parkinson’s disease (PD) is known as a mitochondrial disease. Some even regarded it specifically as a disorder of the complex I of the electron transport chain (ETC). The ETC is fundamental for mitochondrial energy production which is essential for neuronal health. In the past two decades, more than 20 PD-associated genes have been identified. Some are directly involved in mitochondrial functions, such as PRKN, PINK1, and DJ-1. While other PD-associate genes, such as LRRK2, SNCA, and GBA1, regulate lysosomal functions, lipid metabolism, or protein aggregation, some have been shown to indirectly affect the electron transport chain. The recent identification of CHCHD2 and UQCRC1 that are critical for functions of complex IV and complex III, respectively, provide direct evidence that PD is more than just a complex I disorder. Like UQCRC1 in preventing cytochrome c from release, functions of ETC proteins beyond oxidative phosphorylation might also contribute to the pathogenesis of PD.